الأسئلة الصفية: نحو نظرات تطويرية: THE CLASSROOM QUESTIONS: TOWARDS SOME IMPROVING PERSPECTIVES - Bamba, Adama; Wisetrat, Wilailak; Basheer, Basmah (Journal of Islamic Educational Research, 2018)
The current paper attempted to elucidate the classroom questions, in terms of their functions, types and the problematics that teachers face in implementing this teaching strategy in the classroom. Following a documentary method, this paper found that the classroom questions occupy a central position in the teaching activity as well as in the teacher’s competencies. However, the implementation of the classroom questions encounters many shortcomings due to the inability of the teachers to master some pedagogical strategies related to the use of the classroom questions. To contribute in this matter, this paper concluded by proposing some improving strategies in the field of ensuring a better quality of the classroom questions that are meant to develop the learners’ high thinking abilities.